Characterization of endogenous markers of hepatic function in patients receiving itraconazole treatment for prophylaxis of deep mycosis. Issue 3 (March 2023) - Nakatsugawa, Emi; Naito, Takafumi; Imoto, Yumi; Shibata, Kaito; Ono, Takaaki; Kawakami, Junichi
Abstract: Background: Long-term use of itraconazole (ITZ) is associated with a risk of inducing hepatotoxicity. This study aimed to evaluate the associations of plasma concentrations of ITZ and its hydroxylated metabolite (OH-ITZ) with endogenous markers of hepatic function. Methods: Thirty six patients treated with oral ITZ solution for prophylaxis of deep mycosis were enrolled. Plasma concentrations of ITZ and OH-ITZ were determined on the 14th day or later after administration of ITZ. Their associations with endogenous marker levels of hepatic function including plasma coproporphyrin (CP)-I and OATP1B1 genotypes were assessed. Results: The serum level of total bilirubin (T-Bil) was moderately correlated with the plasma concentration of total ITZ (tITZ) and OH-ITZ (tOH-ITZ). T-Bil elevation above 0.3 mg/dL was observed in 19% of patients, although statistically significant difference was not identified. The plasma concentration of tITZ had no correlation with other endogenous markers levels including AST, ALT, albumin, and plasma CP-I. The serum AST and plasma CP-I levels were correlated with the plasma concentration of free OH-ITZ (fOH-ITZ). T-Bil and plasma CP-I, a marker of OATP1B1 activity, were not correlated with each other, and neither was associated with the OATP1B1 genotypes. Conclusions: Plasma ITZ and OH-ITZ had a positive association with T-Bil. The patients with a higher fOH-ITZ level had lower OATP1B1 activity on the basis of plasma CP-I level. ITZ and OH-ITZ have the potential to slightly increase endogenous marker levels of hepatic function, although most likely by different mechanisms.